Virusplot: a web server for viral integration analysis and visualization - Hu, Erqiang; An, Jianhong; Gersten, Adam J; Wu, Nicole; Kawachi, Nicole; Zhu, Jing; Rosenblatt, Gregory; Augustine, Stelby; Smith, Richard V.; Segall, Jeffrey E; Ostrer, Harry; Amelio, Antonio L; et al. (Frontiers in Oncology, 2025)
The integration of viral DNA into the human genome is a critical event in the pathogenesis of various cancers. This process leads to genomic instability, disrupts cellular regulatory mechanisms, and activates oncogenes or inactivates tumor suppressor genes. Despite significant advancements in genome sequencing technologies, there remains a notable lack of computational tools, particularly web-based applications, specifically designed for viral integration analysis and visualization. To address this gap, we present virusPlot, a web server with the following functional modules: (i) automatic retrieval of virus genome sequences and their annotation; (ii) visualization of virus integration locations and read counts through a graphical representation that links viral and host genome integration sites, facilitating the interpretation of integration patterns; (iii) analysis of virus integration hotspots using Fisher’s exact test; and (iv) integration of various functions into an interactive web platform via shinyapp. VirusPlot efficiently processes and visualizes integration data from viruses and host genomes, providing researchers with an intuitive and user-friendly analytical tool that simplifies the complexity of virus integration analysis.